2014
DOI: 10.1158/1055-9965.epi-13-0957
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nicotine Cigarettes: Smoking Behavior and Biomarkers of Exposure among Smokers Not Intending to Quit

Abstract: Background: The U.S. FDA has the authority to limit the nicotine content of cigarettes; however, there are concerns that reduced nicotine cigarettes will be smoked more intensely and, therefore, will increase exposure to toxic chemicals in smoke. This study examined changes in consumer behavior and exposure in response to cigarettes with substantially reduced nicotine content.Methods: Seventy-two adult smokers completed an unblinded trial of reduced nicotine cigarettes. Participants completed a 7-day baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 56 publications
(83 reference statements)
4
44
0
Order By: Relevance
“…At moderate nicotine content, smokers increased daily cigarette consumption but puffed less intensely; at very low nicotine content, smokers’ CPD and total puff volume were similar to use of their own cigarette brand. Harm exposure findings were equally complex: NNAL and cotinine decreased with cigarette nicotine content, but RNC period had no effect on 1-HOP, consistent with other studies (8,9,1113,36). Further, CO boost increased at moderate nicotine content, but decreased during very low nicotine content.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…At moderate nicotine content, smokers increased daily cigarette consumption but puffed less intensely; at very low nicotine content, smokers’ CPD and total puff volume were similar to use of their own cigarette brand. Harm exposure findings were equally complex: NNAL and cotinine decreased with cigarette nicotine content, but RNC period had no effect on 1-HOP, consistent with other studies (8,9,1113,36). Further, CO boost increased at moderate nicotine content, but decreased during very low nicotine content.…”
Section: Discussionsupporting
confidence: 87%
“…Study findings explicate previous work by demonstrating that very low nicotine content cigarettes generally do not increase measures of harm exposure or negative smoking behaviors, despite diverging from prior research (8,9,11) regarding behavioral results at moderate nicotine content. Such discrepancies may be due to study differences in assessment of cigarette consumption (e.g., using spent filters to complement self-report may have increased accuracy over daily dairy methods prone to recall bias), or length of exposure to each nicotine level (e.g., 7-day (11), 1-week (8), and 1-month (9) periods).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Although smokers may attempt to compensate when they first try VLNC cigarettes, numerous studies have shown that most smokers do not compensate after the first few cigarettes5 34 35 and that biomarkers of smoke exposure do not increase when participants are switched to VLNC cigarettes 4 5 8 9 16 17. One limitation of clinical trials suggesting little or no compensation is that smokers could easily purchase normal nicotine cigarettes, although an inpatient study in which participants could only use VLNC cigarettes also demonstrated a reduction in smoke exposure 8.…”
Section: Common Questionsmentioning
confidence: 99%